The Digestive Extramucous one Layer Sutures, with the Technic and Materials employed in Vascular Surgery - Laca, Emilio; Delgado, Bolívar; Gateño, Nisso; Iraola, María L (Cirugía del Uruguay, 1980)
This paper reports the experience of 3 surgeons who have separately performed 100 consecutive sutures of digestive tube by applying vascular suture techniques and material, in extramucous layer. The following aspects should be stressed: The suture should only serve to unite. Technical details: vascular suture materiaf is employed and surgery is performed with the minuteness and care which characterize vascular surgery. Results: low postoperatory morbility, as compared td traditional suture techniques; no deaths attributable to complications arising from suture failure, with technique described.